Neutralizing Effects of Mimosa tenuiflora Extracts against Inflammation Caused by Tityus serrulatus Scorpion Venom. (11th June 2014) - Bitencourt, Mariana Angélica Oliveira; Lima, Maira Conceição Jerônimo de Souza; Torres-Rêgo, Manoela; Fernandes, Júlia Morais; Silva-Júnior, Arnóbio Antônio da; Tambourgi, Denise Vilarinho; Zucolotto, Silvana Maria; Fernandes-Pedrosa, Matheus de Freitas
Abstract : Scorpion bite represents a significant and serious public health problem in certain regions of Brazil, as well as in other parts of the world. Inflammatory mediators are thought to be involved in the systemic and local immune response induced by Tityus serrulatus scorpion envenomation. The aim of this study was to evaluate the effect of extracts of Mimosa tenuiflora on model envenomation. In mice, the envenomation model is induced by Tityus serrulatus venom. Previous treatment of mice with fractions from M. tenuiflora was able to suppress the cell migration to the peritoneal cavity. The treatment of mice with M. tenuiflora extracts also decreased the levels of IL-6, IL-12, and IL-1β . We concluded that the administration of the extract and fractions resulted in a reduction in cell migration and showed a reduction in the level of proinflammatory cytokines. This study demonstrates, for the first time, the anti-inflammatory effect of aqueous extract from the Mimosa tenuiflora plant on T. serrulatus venom.